2017
DOI: 10.1159/000484561
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cosyntropin Stimulation Study and Disease Severity in Children with Fluid- and Catecholamine-Refractory Shock in the Pediatric and Cardiovascular Intensive Care Unit

Abstract: Background: The cosyntropin stimulation study (CSS) measures the patient’s ability to adequately mount a cortisol response. Clinically, CSS results may not be used to guide hydrocortisone use. The objective of this study was to examine how the CSS results are associated with clinical parameters, mortality/disease severity, and use of glucocorticoids in pediatric patients with catecholamine- and fluid-resistant shock. Methods: This was a retrospective cohort study of patients who had a CSS during 2009–2014 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…Aydın et al detected a positive correlation between PRISM III scores and basal cortisol levels in 40 patients who were followed from their first day of admission in the PICU (21). Iyer et al reported a positive correlation between peak cortisol levels and PRISM III scores in children with fluid-and catecholamine-refractory shock; our study is in accordance with these findings (22).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Aydın et al detected a positive correlation between PRISM III scores and basal cortisol levels in 40 patients who were followed from their first day of admission in the PICU (21). Iyer et al reported a positive correlation between peak cortisol levels and PRISM III scores in children with fluid-and catecholamine-refractory shock; our study is in accordance with these findings (22).…”
Section: Discussionsupporting
confidence: 91%
“…Glucocorticoid treatment tends to be administered according to the clinical conditions of patients in the ICU, and not based on the ACTH stimulation test or basal cortisol levels (22). As observed in our study, the basal and stimulated cortisol levels of all patients were reasonable.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, socioeconomic factors affected discharge decisions, with considerations such as transportation and caregiver availability playing significant roles. [8][9][10][11][12][13][14][15] Most of the studies confirm our findings.…”
Section: Discussionsupporting
confidence: 86%
“…A total of 21 observational studies published before 2022 were analyzed, with a total of 2,212 enrolled subjects, of whom 57.97% were male and 42.03% were female. 5,6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The sample consisted of 1,810 subjects with critical illness, including 916 subjects with sepsis and septic shock, and 402 control subjects. The characteristics and outcomes of included studies are shown in Tables 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen of 21 studies stated that there was a relationship between elevated cortisol levels and mortality in critical illness patients, including those with sepsis, as shown in Table 3. 5,6,[13][14][15][16][17][19][20][21][22][24][25][26][27][28][29][30] One study agreed with the statement, but found no relationship between postserum ACTH stimulation test and mortality in critical illness patients. 17 Fourteen studies had mortality percentage data critical illness patients with elevated cortisol levels.…”
Section: Resultsmentioning
confidence: 99%